PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT. BPD BALI CABANG RENON - Ni Luh Ari Cahyani; Gde Bayu Surya Parwita; Putu Agus Eka Rismawan (VALUES, 2022)
Performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. The purpose of the study was to determine the effect of transformational leadership, work motivation and job satisfaction on employee performance. The object of research used in this research is Transformational Leadership, Work Motivation, Job Satisfaction and Employee Performance. The data collection methods used in this study were observation, interviews, and questionnaires. Data analysis used multiple linear regression analysis. The result of the research is that transformational leadership has a positive and significant effect on employee performance at PT. BPD Bali Renon Branch. Work motivation has a positive and significant effect on employee performance at PT. BPD Bali Renon Branch. Job satisfaction has a positive and significant effect on employee performance at PT. BPD Bali Renon Branch